On the comparison of diamond honeycomb and 3D-Kagome structures for 3D printed UAVs - Govdeli, Yunus (2018)
This study elaborates developing two different types of cellular internal structures to improve the bending stiffness and to reduce the weight of a vertical take-off and landing unmanned aerial vehicle (UAV). Whereas the number of different cellular structures is limited in traditional manufacturing techniques, 3D printing not only provides a variety in cellular structures but also allows to manufacture such complex structures efficiently. Since bending of UAV wings can be closely modelled as bending of cantilever beams, 3D printed cantilever beams with two different cellular structures, i.e. diamond honeycomb and 3D-Kagome, are designed and fabricated using acrylonitrile butadiene styrene. Subsequently, they are elaborated based on their bending stiffnesses and relative densities. Based on the experimental results, the honeycomb structure is selected as the wing structure of the prototyped UAV. The results show that the diamond honeycombs can bear the overall loading on the UAV with 31.8% weight reduction when compared to a conventional system consisting of ribs and spars.